SEARLE, John (2015): Seeing Things as They Are: A Theory of Perception. New York: Oxford University Press. - Luis López, Alberto (Daimon Revista Internacional de Filosofia, 2017)
Reseña del libro de John Searle (2015): "Seeing Things as They Are: A Theory of Perception".